Democracy & capitalism : Asian and American perspectives - Robert Bartley et al.. (Institute of Southeast Asian Studies)
Democracy / Chan Heng Chee - American democracy in relation to Asia / Samuel P. Huntington - Capitalism and the role of the state in economic development / Shijuro Ogata - Capitalism, the market mechanism, and the state in economic development / Bartley